Identifying the Impact of Culturally Relevant Pedagogy: Evidence of Academic Risk-Taking in Culturally and Economically Diverse Nova Scotia Classrooms - Mitton, Jennifer; Murray-Orr, Anne (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
This article reports on findings from a qualitative research study investigating ways to support learners from populations who have been historically underserved by the Nova Scotia education system, particularly African Nova Scotian and Mi’kmaq learners, and learners who experience poverty. Working with middle school teachers located in rural schools with a proven track record of enabling students to succeed and thrive, we spent two years in their classrooms observing and documenting pedagogical practices in the teaching of science and social studies. The results of this research not only complement what is known about how to support vulnerable learners in diverse school contexts, but also provide insights into how these teachers created conditions in which students felt able to take risks academically. The findings of this study show how the idea of academic risk-taking can complement, and expand, scholarship on culturally relevant pedagogy.